Disorder of intracellular cobalamin metabolism: Importance of rapid diagnostic illustrated by a case report of early-onset methylmalonic aciduria and homocystinuria, cobalamin C type - Etienne Mondesert; Bastien Baud; Agathe Roubertie; Jean-François Benoist; Pierre-Edouard Grillet; Jean-Paul Cristol; Marie Céline Francois-Heude; Manuel Schiff; Stéphanie Badiou (Heliyon)
Methylmalonic aciduria and homocystinuria, cobalamin C type (cblC), constitute the most common inborn error of intracellular cobalamin metabolism. Here, we report the case of a 6-month-old child, presenting severe subacute neurological decline associated with failure to thrive. Biochemical tests indicated a disorder of intracellular cobalamin metabolism, with elevated urinary and plasma methylmalonic acid levels associated with high plasma homocysteine concentrations, with normal plasma vitamin B12 concentrations. Diagnosis was later confirmed by genetic analysis which identified two pathogenic variants on the MMACHC gene: c.271dupA (p.Arg91lysfs∗14) paternal allele and c.388T > C (p.Tyr130His) maternal allele. The patient responded well to hydroxocobalamin treatment, with a rapid recovery of symptoms and a normal growth at 2.8 years of follow-up. This case illustrates the importance of early diagnosis of cobalamin metabolism disorders by prescribing adequate biochemical tests.